Influence of sowing dates on productivity and profitability of sunflower (Helianthus annuus L.) hybrids in the north-western Himalayas of India - Lalrammawii, C; Vijay, K; Rajeev, Bharat; R S, Sudan; Joy, Samuel MeCarty; Faraaz, Farooq; Hritik, Srivastava; Gurleen, Kaur (Plant Science Today, 2026)
A field investigation was conducted at the Farming System Research Centre, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu, during 2023 and 2024. The study aimed to assess the effect of sowing dates and varietal performance of sunflower on growth and productivity. The experiment was laid out in a factorial randomized block design with three replications, comprised of three sowing dates (10th and 20th February and 2nd March) as factor A and four sunflower varieties (PSH-2080, PSH-1962, DRSH-1 and KBSH-44) as factor B. Recommended doses of nutrients were applied and the soil was sandy clay loam, slightly alkaline and low in available nitrogen and organic carbon. Results revealed that sunflower sown on 10th February recorded significantly superior plant height, dry matter accumulation, leaf area index (at harvest), yield attributes and yield across both years. Among varieties, PSH-2080 performed significantly better as compared to other varieties in terms of productivity. However, DRSH-1 and KBSH-44 recorded higher growth attributes during both the years of investigation respectively. Overall, the sunflower variety PSH-2080 sown on 10th February proved to be the most productive and adaptable under irrigated north-western Himalayan regions.